IMPLEMENTASI PROGRAM OUTBOUND TERHADAP KARAKTER KEPEMIMPINAN SISWA SEKOLAH ALAM ALGIVA - Nuraeni, Siti; Hasanah, Tita; Awaludin S., Muhamad Robie (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
This research aims to determine the implementation of the outbound program on the leadership character of students at Algiva Alam School. This research uses a combination method, namely a combination of quantitative and qualitative research. Validity tests and reliability tests are used to strengthen the instruments used. The objects in the research are class V students. The informants in this research are the school principal and outbound teacher. Data collection methods use observation, interviews and documentation. The data analysis technique uses a leadership character questionnaire and an outbound questionnaire. Based on the calculation results of the reliability test and validity test, it shows leadership character with a result of 0.82 with 10 valid questions. The outbound questionnaire showed 1.00 with 12 valid questions. The results of the reliability coefficient criteria show 0.80 ≤ r < 1.00 with a very high interpretation value. In percentage terms, the results of the leadership character questionnaire are 70% and the results of the outbound questionnaire are 78%. The results of the research show that the implementation of the outbound program on the leadership character of Alam Algiva School students is responsible, trustworthy, firm, intelligent, initiative, honest, consistent, straightforward and fair. The assessment is carried out by the outbound teacher before the activity, during the activity and at the end of the outbound teacher's activity by providing reflection to each student.